Synthesis, Characterisation Of Stilbene–Arylcinnamide Hybrids And Cytotoxic Studies Against Lung Cancer Cell A549 - Mohd Zaki, Nurain Syazwani (2024)
Numerous anticancer drugs have been designed from natural products. Several compounds derived from nature such as alkaloid, flavonoid, cinnamic acid and stilbene, were reported to possess various biological properties primarily as an anticancer agent. In this study, a total of 24 compounds of a new hybrid series has been designed and synthesised, resulting from the coupling of stilbene and arylcinnamide scaffolds. All synthesised stilbene-arylcinnamide hybrids were obtained in 42-80% yield. Elucidation and characterisation of these hybrids have been validated using Fourier Transform Infrared (FT-IR), Nuclear Magnetic Resonance (NMR) spectroscopy and High-Resolution Mass Spectrometry (HRMS). The cytotoxicity against human lung cancer A549 cell line was assessed by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assay, using cisplatin as the positive control. Particularly, compounds 66b and 74b have displayed potent activities on A549 cancer cells with IC50 value of 20.0 μM and 19.9 μM, respectively. This result is comparable to cisplatin with IC50 value of 19.9 μM after 72 hrs post-treatment. The structural activity relationship (SAR) analysis revealed that the presence of an isopropyl group attached to para-position of stilbene phenyl ring (ring A) of compounds 66b and 74b was crucial for a good cytotoxic effect on A549 cells. Additionally, 4-methyl group as the substituents on cinnamide phenyl ring (ring C) contributed to an innumerable cancer cell death.